Mapk Signaling Is Required for Dedifferentiation of Acinar Cells and Development of Pancreatic Intraepithelial Neoplasia in Mice - Collins, Meredith A. (2013)
BACKGROUND & AIMS: Kras signaling via mitogen-activated protein kinase (MAPK) is highly up-regulated in pancreatic cancer cells. We investigated whether Mapk signaling is required for the initiation and maintenance of pancreatic carcinogenesis in mice. METHODS: We studied the formation and maintenance of pancreatic intraepithelial neoplasia (Pan-INs) inp48Cre; TetO-KrasG12D; Rosa26rtTa-IRES-EGFP (iKras*) mice and LSL-KrasG12D mice bred with p48Cre mice (KC mice). Mice were given oral PD325901, which is a small-molecule inhibitor of Mek1 and Mek2 (factors in the Mapk signaling pathway), along with injections of cerulein to induce pancreatitis. Other mice were given PD325901 only after Pan-INs developed. Pancreatic tissues were collected and evaluated using histologic, immunohistochemical, immunofluorescence, and electron microscopy analyses. Acinar cells were isolated from the tissues and the effects of Mek1 and 2 inhibitors were assessed. RESULTS: PD325901 prevented PanIN formation, but not pancreatitis, in iKras* and KC mice. In iKras* or KC mice given PD325901 at 5 weeks after PanINs developed, PanINs regressed and acinar tissue regenerated. The regression occurred through differentiation of the PanIN cells to acini, accompanied by re-expression of the acinar transcription factor Mist1. CONCLUSIONS: In iKras* and KC mice, Mapk signaling is required for the initiation and maintenance of pancreatic cancer precursor lesions. Mapk signaling promotes formation of PanINs by enabling dedifferentiation of acinar cells into duct-like cells that are susceptible to transformation.